Strategic Business Management in the Digital Economy - Tetiana Grynko; Tetiana Hviniashvili (Challenges and Issues of Modern Science)
The work substantiates the relevance of issues of strategic management of enterprises in modern conditions of globalization and digital transformation of society. The peculiarities of the functioning of modern enterprises under the influence of factors of the digital economy are determined, which requires the adaptation of traditional models of strategic management and their combination with new approaches in order to ensure the competitiveness of enterprises on the market. It is substantiated that an important aspect of strategic management is the effective use of limited resources, which determines a successful enterprise management strategy. The work substantiates the relevance of issues of strategic management of enterprises in modern conditions of globalization and digital transformation of society. The peculiarities of the functioning of modern enterprises under the influence of factors of the digital economy are determined, which requires the adaptation of traditional models of strategic management and their combination with new approaches in order to ensure the competitiveness of enterprises on the market. It is substantiated that an important aspect of strategic management is the effective use of limited resources, which determines a successful enterprise management strategy. The work substantiates the relevance of issues of strategic management of enterprises in modern conditions of globalization and digital transformation of society. The peculiarities of the functioning of modern enterprises under the influence of factors of the digital economy are determined, which requires the adaptation of traditional models of strategic management and their combination with new approaches in order to ensure the competitiveness of enterprises on the market. It is substantiated that an important aspect of strategic management is the effective use of limited resources, which determines a successful enterprise management strategy.